2010
DOI: 10.1002/pon.1844
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions as part of breast cancer rehabilitation programs? Results from a systematic review

Abstract: Objective: This systematic review aimed to determine the effectiveness of psychoeducation, cognitive behavioural therapy (CBT) and social support interventions used in the rehabilitation of breast cancer (BC) patients.Methods: We conducted a systematic literature search to identify randomised controlled trials of female BC patients who underwent different psychosocial interventions during or after primary cancer treatment. The methodological quality of all studies was independently assessed by two reviewers. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 42 publications
1
104
0
18
Order By: Relevance
“…There are only a few studies evaluating psychosocial interventions as breast cancer rehabilitation programs; however, psychoeducation, cognitive behavioral therapy and social and emotional support may be beneficial for improving QOL [52].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies evaluating psychosocial interventions as breast cancer rehabilitation programs; however, psychoeducation, cognitive behavioral therapy and social and emotional support may be beneficial for improving QOL [52].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in levels of QOL and in strength of associations between QOL and social support indicate that social support-QOL relationships should be analyzed in a context of a specific type of cancer. Therefore, in line with previous systematic reviews evaluating psychosocial predictors of QOL among cancer patients [15], the present review focuses on the associations observed for one type of cancer. In particular, we investigated lung cancer, which is among the most common cancer among men, increasing in prevalence among women [16], causing functional limitations more frequently than several other types of cancer [14], and accounting for the largest number of cancer-related deaths in the European Union [16].…”
Section: Introductionmentioning
confidence: 99%
“…Los descriptores utilizados para este fin fueron: "cancer and quality of life", "cancer and quality of life and review", "cancer and psychological intervention" y "cancer and psychological intervention and review". Además, con el objetivo de abarcar otros trabajos, incluso previos al año 2000, se han tenido en cuenta distintas revisiones publicadas por otros autores (5,7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) . La revisión se realizó partiendo de los artículos originales, escritos en inglés y español y de los resúmenes ofrecidos en las bases de datos, en los que se especificase el procedimiento y la muestra del estudio.…”
Section: Métodounclassified